IMPACT OF COVID-19 ON CARDIOVASCULAR COMPLICATIONS IN TYPE 2 DIABETES - D.K, Najmutdinova; A, Urunbayeva D.; G, Sadikova N; A, Pulotova S (Journal of Medical Genetics and Clinical Biology, 2024)
Background: The COVID-19 pandemic, instigated by the SARS-CoV-2 virus, has precipitated unprecedented global health and economic challenges since its identification in late 2019. Specific Background: To date, over 770 million confirmed COVID-19 cases and millions of deaths have been documented worldwide. Individuals with Type 2 Diabetes Mellitus (T2DM) are particularly vulnerable, exhibiting an elevated risk of severe illness and mortality due to exacerbated inflammatory responses and frequent comorbidities such as cardiovascular disease, hypertension, and obesity. Knowledge Gap: Despite the known risks, the precise molecular interactions between SARS-CoV-2 and host cells, and how these may be modified by diabetes and its comorbidities, remain inadequately understood. Aims: This study aims to elucidate the molecular mechanisms underpinning the interaction between SARS-CoV-2 and human cells, with a specific focus on how T2DM influences these interactions. Results: Preliminary findings indicate that the presence of T2DM amplifies the inflammatory response to SARS-CoV-2 infection, likely through altered receptor interactions and exacerbated immune responses. Novelty: This research provides new insights into the differential impact of SARS-CoV-2 on diabetic versus non-diabetic patients, highlighting the role of diabetes-induced alterations in viral pathogenesis. Implications: Understanding these mechanisms is crucial for developing targeted therapeutic and preventive strategies to mitigate the heightened risk faced by individuals with T2DM during pandemics, thereby informing public health policies and clinical practices.